Having it all : what data tells us about women's lives and getting the most out of yours - Low, Corinne (Flatiron Books, 2025)
"A Wharton economist's radical framework for empowering women to design a life that goes beyond the work-life binary to create true joy, balance, and fulfillment. To be a woman in America today is to be chronically tired. We face unsustainable demands on our time and efforts in every sphere. Traditional advice urges us work harder, optimize better, and, when all else fails, "self-care." The implicit message is that it is our fault that we are overwhelmed, that we must be doing something wrong. This, says economist and professor Corrine Low, couldn't be further from reality. At Wharton, she studies the decisions that shape women's lives and the economic and societal constraints they face when making them. And what her research has demonstrated, time and again, is that unseen economic forces have created an environment that is openly hostile to the needs of women. Indeed, her research highlights just how many additional factors women must consider as they navigate a future. Because of a few biological realities, and a lot of imbalanced cultural and institutional norms, women face a unique level of complexity and potential repercussions when making decisions such as whether or not to obtain an advanced degree, what type of career to pursue, when or whether to get married and/or have kids, or even where they should live. Now, in Having It All, Low poses a radical new framework for navigating these decisions. For too long, Low says, women have been expected to accept labor-intensive, unsustainable deals in all areas of work and life. This book asks the question: What would it look like if we stopped assuming the problems in women's lives are caused by women's choices, and started looking instead at the structural, economic, and biological factors that are forcing and constraining those choices in the first place? And what if, in doing so, we could learn to negotiate new deals that don't leave us feeling so depleted? In the same way that behavioral psychologists like Daniel Kahneman and Dan Ariely have sought to understand the hidden factors and biases that cause people make mistakes at the bank or the grocery store, economist Corinne Low investigates how the most significant decisions in women's lives are shaped by overlooked internal and external factors. The result is a book that offers readers a guide to getting the best deal for their lives and careers in a world full of constraints. It is also a call to action for firms, policymakers, and anyone else with an iota of power to get to work on the tough job of changing these constraints instead of the easier one we seem to default to: criticizing women. This book is not about optimizing. Women are already optimized. Consider it the essential economic textbook for life as a woman-but hopefully, a little more fun"-- Provided by publisher.